1990
DOI: 10.1007/bf01064915
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians' self-reported reactions to psychiatric emergency patients: Effect on treatment decisions

Abstract: Masters-level social work clinicians at two urban psychiatric emergency services self-rated their cognitive reactions and conscious feelings toward a total of 783 patients. Negative self-reported affect toward patients was related to their displaying overt psychotic symptoms, having a final diagnosis of substance abuse, being impulsive, unemployed, or having a history of criminal behavior. However, clinicians' reactions did not enter into the model predicting hospitalization, which included opinion of family a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 13 publications
1
27
0
Order By: Relevance
“…The results of the present study found a significant weak relation between insight score and both number of previous admissions and longer previous hospital stay. This is in agreement with other studies which have found that deficits in illness awareness are associated with greater number and longer duration of hospitalization (24)(25)(26) . Awareness seems to grow only partially with clinical improvement and appears to diminish progressively with the repletion of episodes and numbers of previous admissions (27)(28)(29)(30) .…”
Section: Resultssupporting
confidence: 93%
“…The results of the present study found a significant weak relation between insight score and both number of previous admissions and longer previous hospital stay. This is in agreement with other studies which have found that deficits in illness awareness are associated with greater number and longer duration of hospitalization (24)(25)(26) . Awareness seems to grow only partially with clinical improvement and appears to diminish progressively with the repletion of episodes and numbers of previous admissions (27)(28)(29)(30) .…”
Section: Resultssupporting
confidence: 93%
“…1). Data were extracted from ten studies (3/5/2 of low/intermediate/ high quality, respectively) and details of each study (Barzilay et al, 2018;Colson et al, 1986;Dressler, Prusoff, Mark, & Shapiro, 1975;Gillig, Hillard, Deddens, Bell, & Combs, 1990;Hawes et al, 2017;Perry, Bond, & Presniak, 2013;Rossberg & Friis, 2003;Soulié, Bell, Jenkin, Sim, & Collings, 2018;Yaseen et al, 2013;Yaseen et al, 2017) are available in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Around 700 health professionals participated in the ten studies and their countertransference was measured from clinical encounters with 2247 patients. Patients came from outpatient/psychotherapeutic clinics (Barzilay et al, 2018;Perry et al, 2013;Soulié et al, 2018;Yaseen et al, 2013), psychiatric hospitals (Colson et al, 1986;Rossberg & Friis, 2003;Yaseen et al, 2013;Yaseen et al, 2017) and emergency wards (Dressler et al, 1975;Gillig et al, 1990). Countertransference was measured based on a mid-or long-term therapeutic relationship (Colson et al, 1986;Perry et al, 2013;Rossberg & Friis, 2003;Soulié et al, 2018;Yaseen et al, 2013;Yaseen et al, 2017) or on a single consultation (Barzilay et al, 2018;Dressler et al, 1975;Gillig et al, 1990;Hawes et al, 2017).…”
Section: General Description Of Studiesmentioning
confidence: 99%
“…People who struggle with suicidality have been labeled by the general public as attention‐seeking, weak, and cowardly (Sheehan, Corrigan, Al‐Khouja, & the Stigma of Suicide Research Team, ; Sudak, Maxim, & Carpenter, ). Despite the intuitive view that health care workers are more compassionate and understanding toward individuals experiencing suicidality, such professionals are not immune to endorsing stigmatizing attitudes (Gillig, Hillard, Deddens, Bell, & Combs, ; Norheim, Grimholt, & Ekeberg, ). Individuals with a history of suicidal behavior report encountering stigma in their interactions with mental health professionals, including counselors, therapists, and psychiatrists (Frey, Hans, & Cerel, ).…”
Section: Obstacles To Service Provisionmentioning
confidence: 99%